Pemanfaatan Akuifer untuk Pemenuhan Kebutuhan Air Bersih di Kawasan Blang Bintang, Aceh Besar - Zul Fadhli, Zul Fadhli Zul Fadhli; Miska, Layna; Marwan, Marwan; Safitri, Rini; syukri, Muhammad; marvita, Yurda; Anda, Sabrian tri; Azmi, Nurul (Universitas Syiah Kuala, 2024)
Groundwater is water that sourced from rainwater, river water and others which seeps into the ground and accumulates in a layer called an aquifer. Estimation of the distribution and identification of aquifer geometry is carried out to assist the people of Cot Madhi Village in an effort to design the depth of drilling to obtain water that will be used for their basic and supporting needs. In this measurement, the 1D resistivity geoelectric method is used to determine the resistivity value changes of the rock layer which serves to identify the type of aquifer and the depth of the aquifer for efficient drilling of well activities. The measurement uses Supersting instruments with Wenner-Schlumberger cable configuration. The results showed subsurface resistivity values in the measurement area between 3.4 - 112.1 m. The penetration depth in this measurement is up to 165 meters deep. The resistivity model profile indicates a very economical water layer (aquifer) with a resistivity of 27.3 m located at a depth of 54-84 meters with a thickness of 30 meters. This research found a potential aquifer layer as a source of clean water.